Awareness during anesthesia in cocaine addicters: concerning about chemical interactions - Amorim Melo Moreira, Erika; Ribeiro Moura Barbosa, Kelly; Carvalho Gonçalves, André; Corral Vasquez, Elisardo; Henrique cassaro Lirio, Pedro; Magnago Santos, Joao (Seven Editora, 2023)
The interaction between cocaine and anesthetic drugs has been known since 1884 when it was first used for the treatment of morphine addiction and as a local anesthetic. Due to a large number of users of the substance, the interaction with anesthetic drugs has been frequent and it has been seen that many drugs have their effects altered in the presence of cocaine. Through a bibliographical survey in PubMed and CrossRef, aiming to highlight the risks of this interaction and conduct in cases of elective surgeries in these patients, we conducted this study and verified that so many drugs have to be avoided due to their interaction effects, but in the absence of clinical signs of intoxication, screening becomes ineffective.DOI: https://doi.org/10.56238/devopinterscie-126